Evaluación del efecto de la de la posicion de la mazorca en el árbol y de la semilla dentro del fruto, en el crecimiento de plantulas de cacao(Theobroma cacao L.), Fase de vivero" - Guerra Briones, Guido Gonzalo (2012)
The present investigation was performed in the farm "Selva Alegre (Happy Forest), which is, localized in the San Carlos County, in Quevedo City, Province of Los Ríos, in km. 1 from via San Carlos - Quevedo. Its geografical location is 01°06’13” south latitude, and 79°29’ west longitude, on a height of 75 msnm. We used a factorial formula P=2 (Position of the cob in the plant, p1=high; p2=low) x S=3 (position of seed on cob, s1= proximal; s2=central; s3=distal), in a complete random design with four repetitions for each treatment, the experimental unit was formed of 50 seedlings. The dependent variables were constructed from the weight of the seed grains(gr.), percentage of germination(%), diameter of the stem(mm) after 30, 60 and 90 days, height of the plant(cm.) after 30, 60 and 90 days, number of leafs after 30, 60 and 90 days, length of each leaf(cm.) after 30, 60 and 90 days, width each leaf(cm.) after 30, 60 and 90 days, size of the pivoting root(cm.) after 90 days, volume of the root(mm.) after 90 days and number of secondary roots after 90 days. As general objective: To study the effect of the positioning of the cob in the tree (stem and branch), and the effect of the seed positioning in the fruit (proximal side, central and distal), in the growth of the seedlings of Cocoa in the nursery phase. ..............